Integrasi Nilai Keberlanjutan dan Keagamaan dalam Investasi Syariah: Kajian Konseptual dalam Kerangka Pasar Modal Syariah - Suparman; Vera Nopiyani; Dini Selasi (Journal of Economics, Management, and Accounting, 2025)
This study explores the conceptual integration of sustainability principles and religious values within Islamic investment, emphasizing the intersection between Environmental, Social, and Governance (ESG) standards and the objectives of maqāṣid al-sharī‘ah. Through an extensive literature-based analysis, the research highlights how Islamic capital market instruments such as sharia-compliant equities, sukuk, and ESG-aligned Islamic funds embody ethical accountability while responding to the growing global demand for responsible finance. Empirical data from the development of Indonesia’s Islamic capital market, including the ISSI index, sharia market capitalization, and global sharia ESG fund performance, reveals strong structural potential for sustainable Islamic investment models. The findings demonstrate that sharia-based instruments offer moral alignment and competitive financial resilience in periods of economic uncertainty. Despite this progress, challenges remain, particularly regarding inconsistencies in ESG assessment methods, risks of symbolic compliance, and the need for deeper integration between sharia governance and sustainability reporting. This study underscores the importance of developing a unified ESG–maqāṣid framework and strengthening regulatory transparency to support the advancement of ethical, accountable, and sustainability-driven Islamic financial ecosystems